2010
DOI: 10.1002/ejic.201000030
|View full text |Cite|
|
Sign up to set email alerts
|

Mesoporous CeO2 Hollow Spheres Prepared by Ostwald Ripening and Their Environmental Applications

Abstract: CeO 2 hollow spheres (250-350 nm in diameter), with mesoporous shells of approximately 50 nm, were synthesized by a one-pot, template-free hydrothermal method. X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), transmission electron microscopy (TEM), scanning electron microscopy (SEM), high resolution transmission electron microscopy (HRTEM), and nitrogen adsorption-desorption measurements were used to characterize the products. The for-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(87 citation statements)
references
References 51 publications
1
86
0
Order By: Relevance
“…It appears that the adsorption capacity of Congo red by the as-synthesized α-FeOOH hollow spheres is significantly higher than that of most similar materials reported previously. [18,[33][34][35]55,56,61,63] prolonged hydrothermal treatment, the adsorbed precursors will further crystallize into rod-or sheet-like nanostructures, forming a complete hierarchical shell.…”
Section: Doi: 101002/adma201104599mentioning
confidence: 99%
“…It appears that the adsorption capacity of Congo red by the as-synthesized α-FeOOH hollow spheres is significantly higher than that of most similar materials reported previously. [18,[33][34][35]55,56,61,63] prolonged hydrothermal treatment, the adsorbed precursors will further crystallize into rod-or sheet-like nanostructures, forming a complete hierarchical shell.…”
Section: Doi: 101002/adma201104599mentioning
confidence: 99%
“…under oxidizing and reducing conditions, respectively [2,3]. However, the CeO 2 is not a promising candidate for catalytic samples mainly due to its low catalytic activities [4][5][6][7][8][9]. Numerous reports have shown that the activity of ceria in total oxidation reactions is greatly enhanced by transitional metals like Co, Cu, Ti, Ni, and so on [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…CR dyes from textile and dyeing industries are causing severe environmental problems and are banned in many countries because of health concerns. However, the traditional physical, chemical and biological means of wastewater treatment often have little degradation effect on this anionic secondary diazo dye pollutant due to their complex aromatic structures, which provide them physicochemical, thermal and optical stability [25,26]. Therefore, there is an urgent requirement for development of innovative, but low-cost processes, by which dye molecules can be removed.…”
Section: Introductionmentioning
confidence: 99%